Marcadores nutricionais e de expressão gênica associados com o prognóstico na infecção por SARS-CoV-2 em idosos - Lermen, Fernanda Muller (2022)
According to the World Health Organization, most people infected with the SARS-CoV-2 virus will experience mild to moderate respiratory disease, the COVID-19, and will recover without the need for special treatment, but older people and people with underlying medical problems are more likely to have a worse prognosis. Human aging is a natural, non-pathological biological process and nutritional status plays a crucial role in maintaining immune function. Nutrition is a key determinant to health. The current COVID-19 pandemic is a major public health issue. Due those facts, this research goal was to investigate possible gene expression markers associated with nutritional status of elderly patients with SARS-CoV-2 positive diagnosis as protective or aggravation in the outcome of COVID-19. As investigation method there were collected sociodemographic data, past medical history in medical records, anthropometric measurements and for gene and biochemical expressions analyses there was collected a peripheral blood sample. Forty-three elderly patients were evaluated as they were admitted at PUCRS’s Hospital São Lucas in the city of Porto Alegre, all of them with a positive diagnosis for COVID-19, between January and April 2021. With significant differences among two groups scales: Normalcy BMI < 27kg/m² (n=22) vs. Overweight BMI >27 (n=21), p=0,00001. The COVID-19 positive diagnosed elderly, it was observed in the overweight and whit more abdominal fat, a combination with longer hospitalization (although not significant), more time in oxygen and worst disease gravity than normal nutritional state group. Comparing gene expressions from the patients with and without overweight, it was observed 10,77 times increase in gene TNF-α relative expression for the overweight patients comparing them with the normal classified profile. Analyzing patients that showed low D-Vitamin levels, there was an increase in gene IL-6 expression (4.87 times) when compared to the patients with a satisfactory vitamin serum level. Due those facts, stands out that accumulation of visceral fat is associated to COVID-19 aggravation and how appropriate D-vitamin levels are necessary for modulation of innate and adaptative immunity.